La liberté d'expression commerciale - Binette, André (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1987)
The Quebec Court of Appeal has recently decided that commercial speech is protected by s. 2 of the Canadian Charter of Rights and Freedoms and by s. 3 of the Quebec Charter of Human Rights and Freedoms. This article tries to mesure the significance of this judicial extension of the constitutional protection of freedom of speech. Canadian case-law is examined as well as the more important decisions of the Supreme Court of the United States. An attempt is made to reveal the conflict injudicial values and political philosophy that underlies the debate over commercial speech. This conflict revolves around the constitutional relationship between law-makers and the courts on matters of social and economic policy. The suggestion is made that commercial speech is an intellectual and legal vehicle for the political objectives of the New Right. The author concludes that whatever the proper distribution of constitutional authority on the subject may be in the U.S., a different social configuration in Canada should lead our courts to a very careful consideration of the American cases.